Utilization of Malaysian low grade iron ore as medium for ammonia decomposition - Othman, Nur Ezzah Faezah; Purwanto, Hadi; Mohd. Salleh, Hamzah (Asian Research Publishing Network (ARPN), 2015)
Hydrogen has been regarded as the new energy source due to its cleanliness, fast energy cycle and convenience of energy conversion. Hydrogen storage and transportation difficulties have become major drawbacks in hydrogen economy. Conventional process of steam reforming produces large amount of CO as byproduct. Thus, ammonia has attract worldwide attention as new alternative for hydrogen storage as ammonia decomposition yields H2 and N2 as byproduct without any CO emissions. Low grade ore is used as medium for enhancing ammonia decomposition. This paper presents the study of low-grade iron ore as medium for ammonia decomposition. Malaysian low-grade iron ore was taken as the raw material in this experiment. Ammonia decomposition over iron ore medium were studied at temperature of 500-700°C. The nitriding potential of ore was also studied.